Montenegro : 2018 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Montenegro's economy is growing strongly, boosted by the implementation of large investment projects, including the construction of the Bar-Boljare highway. Growth should continue over the medium term, albeit at a more moderate pace as highway construction ends. The IMF staff projects the economy to expand by 3 percent in 2018 and 2.5 percent in 2019, with fiscal consolidation also acting as a moderate drag on growth. Although the implementation of large publicly financed infrastructure projects has added to economic growth, the accompanying use of fiscal resources has contributed to a large increase in government debt. Economic growth should remain strong in 2018, notwithstanding fiscal consolidation, and maintain momentum over the medium term.